Customer Satisfaction with PLN Mobile Application at PT PLN (Persero) ULP Samarinda Ilir: A Qualitative Study - Darmawan Aprianto; Martin Pongsonggo; I Made Suparta; Endah Budiarti (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
PLN Mobile is a digital service platform developed by PT PLN (Persero) to facilitate customer access to electricity services, including bill payments, token purchases, service requests, and complaint handling. Despite supporting the company's digital transformation, users continue to experience system instability, slow response times, login failures, and limited responsiveness of complaint features. This study aims to analyze customer satisfaction with the PLN Mobile application among users of PT PLN (Persero) ULP Samarinda Ilir by examining perceived usefulness, ease of use, system quality, and service quality. A qualitative case study approach was employed. Data were collected through in-depth interviews, observations, and documentation involving 15 customers selected using purposive sampling. Data were analyzed using the Miles and Huberman interactive model and thematic coding. The findings indicate that users are generally satisfied with PLN Mobile, with perceived usefulness emerging as the strongest determinant of satisfaction due to its convenience, time efficiency, and accessibility. However, system quality remains the primary challenge because of application errors, slow performance, and login disruptions. The study concludes that while PLN Mobile provides substantial functional benefits, improvements in system reliability, complaint responsiveness, and feature optimization are essential to enhance customer satisfaction and encourage sustained application use.